1985
DOI: 10.1113/jphysiol.1985.sp015623
|View full text |Cite
|
Sign up to set email alerts
|

The transneuronal induction of sprouting and synapse formation in intact mouse muscles.

Abstract: SUMMARY1. The pattern of innervation to intact peroneal and extensor digitorum longus muscles of normal and experimental young adult mice was studied by light microscopy after staining neuromuscular junctions by a combined silver-cholinesterase stain.2. Spontaneous sprouting and synapse formation occur in intact muscles of normal mice. In about 7 % of the junctions, sprouts contribute to the innervation of muscle fibres already innervated by their parent axons. 3. Axotomy of the sciatic nerve in one hind limb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 21 publications
(44 reference statements)
4
28
0
Order By: Relevance
“…To the extent that this possibility may be true, the conclusions from the present studies must be qualified. Chronic axonal transections of the type used in the present study can have effects both on those neurons that have their axons cut and on those transynaptic to the affected neuron (Anderson and Flumerfelt 1986;Carlson et al 1976;Farel 1980;Rosenthal and Cruce 1984;Rotshenker and Tal 1985). Axotomy can induce both morphological (Cruce 1974;Rosenthal andCruce 1984) andphysiological (Carlson et al 1976;Farel 1980) changes in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that this possibility may be true, the conclusions from the present studies must be qualified. Chronic axonal transections of the type used in the present study can have effects both on those neurons that have their axons cut and on those transynaptic to the affected neuron (Anderson and Flumerfelt 1986;Carlson et al 1976;Farel 1980;Rosenthal and Cruce 1984;Rotshenker and Tal 1985). Axotomy can induce both morphological (Cruce 1974;Rosenthal andCruce 1984) andphysiological (Carlson et al 1976;Farel 1980) changes in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of nerve injury on contralateral motoneurons in rodents was initially reported by Rotschenker & Tal (1985), who suggested that motoneurons contralateral to an axotomized motor nerve sprouted in response to a transneuronal signal from the injured neurons mediated through the spinal cord. More recently, in models of unilateral nerve injury and neuropathic pain, bilateral changes have been reported in nociceptive thresholds (Kim & Chung, 1992), protein kinase C levels and spinal cord metabolic activity, as assessed by ['4C] 2-deoxyglucose uptake (Mao, Mayer, Hayes & Price, 1993), and opioid receptor binding (Stevens, Kajander, Bennett & Seybold, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, these phenomena have been demonstrated either by changes in the pattern of the lamination of afferent systems at the light microscopic level, or by alterations in the distribution of synaptic contacts detected in the electron microscope (for reviews see Cotman er al., 1981;Cotman and Anderson, 1988;Goldberger and Murray, 1988). By contrast, the complete description of the emergence, the course, and the pattern of terminal branching of newly formed axons has never been provided in the adult brain, although such a picture is available for plastic phenomena in the peripheral nervous system (Edds, 1953;Slack et al, 1979;Rotshenker and Tal, 1985;Rotshenker, 1988) and the developing visual system (Robson et al, 1978). The olivocerebellar system provides a favourable model of investigation because of its stereotypic organization, which resembles that of the motor unit.…”
Section: Introductionmentioning
confidence: 91%